(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
According to Mirziyoyev Shavkat Miromonovich, President of the Republic of Uzbekistan, Commander-in-Chief, the great history of the Uzbek people, great statesmanship and the creation of their own culture. In this world, the greatest, most noble and sacred task of a husband is to protect his family, homeland and people. One of the leading, main components of high spirituality is patriotism. The feeling of patriotism is not a theoretical, scientific or practical process focused on one particular area of society. The feeling of patriotism is a representative of every field of society, regardless of the language, religion, gender, social origin of a member of the community living in the same country, a builder, doctor, teacher, law enforcement officer, worker, craftsman and several others. We can expect real patriotism from people who can patiently endure all the difficulties and hardships, who love their profession with their whole body. Patriotism is not enough to say only one word or beautiful words. Therefore, they approach and interpret the concept of patriotism from different angles. In our opinion, patriotism means that a person values his motherland and spends his energy and energy for this motherland, regardless of its field. Although this definition does not cover all aspects of patriotism, the definition is correctly understood if the word patriotism is approached in a broad sense.